Study of B+c → χcπ+ decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Esen, Sevda; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2024)
A study of of B+c → χcπ+ decays is reported using proton-proton collision data, collected with the LHCb detector at centre-of-mass energies of 7, 8, and 13 TeV, corresponding to an integrated luminosity of 9 fb−1. The decay B+c → χcπ+ is observed for the first time, with a significance exceeding seven standard deviations. The relative branching fraction with respect to the B+c → J/ψπ+decay is measured to beBBc+→χc2π+BBc+→J/ψπ+=0.37±0.06±0.02±0.01